Epidemiological Profile of Twice per Week Hemodialysis Patients of Top Referral National Hospital in Indonesia - Lucky Aziza Bawazier (Journal Kedokteran Indonesia, 2018)
Data regarding the epidemiology and laboratory test results of end-stage renal disease (ESRD) patients on twice per week hemodialysis in Indonesia remain limited. This study was conducted to describe the epidemiological and laboratory profiles of ESRD patients undergoing hemodialysis twice a week. This was a cross-sectional study in which the medical records data of all ESRD patients on hemodialysis at Cipto Mangunkusumo Hospital in 2017. Of 145 subjects, 51% were male. The mean age was 50.1 (SD 13.5) years and the mean body mass index (BMI) was 23.1 kg/m2 (SD 4.8). The aetiology of ESRD in these patients was primarily hypertension (40.7%). There was a significant difference in systolic blood pressure (SBP) and diastolic blood pressure (DBP) before and after hemodialysis (p=0.001 and p<0.001) The mean estimated glomerular filtration rate (eGFR) was 4.3 mL/min/1.73 m2 (SD 2.2) and significantly different between those <60 years old and ≥60 years old (p=0.004). In addition, there was an association between uric acid and post-hemodialysis SBP (p = 0.02). It is concluded that age and sex distribution played a significant role in determining epidemiological profile patients undergoing twice per week hemodialysis.